Colostrogenesis during an induced lactation in dairy cattle. Issue 2 (15th May 2014) - Stark, A.; Wellnitz, O.; Dechow, C.; Bruckmaier, R.; Baumrucker, C.
Summary Colostrum immunoglobulin G (IgG) is of major importance for the newborn calf because epitheliochorial placentae do not provide transport in utero. The formation of colostrum occurs in the later stages of pregnancy. Our objectives were to induce lactation in non‐pregnant dairy cows and (i) to determine the changes of IgG in serum and mammary secretions during the induction process and (ii) to establish α‐lactalbumin (αLA) and prolactin (Prl) alterations to monitor the changing mammary epithelial tight junction status and development pattern. Estradiol‐17β (E2) and progesterone (P4) injections in a 1–7 days series were combined with a 3‐day injection series (day 21–23) of dexamethasone (DEX). Blood and both front quarter secretion samples were collected daily. Milking started 24 days after the start of the experiment. Results show that the mammary secretory IgG1 was increased at >7 days after the start of steroid injections and depicted a bimodal pattern reaching a high of 16 mg/ml at 21 day compared with 3.2 mg/ml in the serum. There was a small increase in secretory IgG2 that did not correlate with tight junction status, but never reached the serum concentration. The injections of DEX resulted in constriction of tight junctions. Secretory αLA was immediately increased with steroid injections, dropped precipitously after 7 days and then began a steady increase until the start of milking. Changes in serum αLA are related to mammary tight junctions while serum Prl gradually increased from 30 to >60 ng/ml after the steroid injections stopped. These results provide insights into the mechanisms and timing of colostrogenesis during an induced lactation protocol.